29.3k views
3 votes
Which is the simplified form of the expression (6^-4)^-9/6^6

2 Answers

4 votes

Answer:

Should be 6^30

Explanation:

User Andrew Stakhov
by
5.4k points
4 votes

Given expression:
(((6^(-4))^(-9)))/(6^6).

First we would apply exponents of exponent rule on the top.


(a^m)^n= a^(m* n)

Therefore,


((6^(-4))^(-9)) = (6)^(-4* -9) = (6)^(36)

=
(((6^(-4))^(-9)))/(6^6) = (6^36)/(6^6)

Applying quotient rule of exponents.


(a^m)/(a^n) = a^(m-n)


Therefore \ (6^(36))/(6^6) =6^(36-6)

=
6^(30)

Therefore,
6^(30) is the simplified form of the expression
(((6^(-4))^(-9)))/(6^6).

User Greg Valvo
by
5.6k points